Determinant factors for the expansion of informal settlement in Gondar city, Northwest Ethiopia - Endalew Terefe Alene (Journal of Urban Management, 2022)
This study examines determinant factors for the expansion of informal settlements in Gondar, a historical city in Ethiopia. In order to address this study objective, quantitative data were employed from 196 randomly selected households in four sites. The study indicated that a single factor is not determinant for the expansion of informal settlements in the city. The results of the study revealed that socio-economic, political and legislative, administrative, and demographic factors are statistically significant. These four dimensions together accounts 61.4 percent of all factors that facilitate the formation of informal settlement in Gondar city of Ethiopia. More specifically, socio-economic dimension is the first influential factor with 30.9%; political and legislative dimension is the second dominant factor with 15.7% followed by administrative dimension (10.2%); and demographic factors are contributed the least(4.6%) for the expansion of informal settlements. The study emphasized the need to implement appropriate urban planning, land and housing policy aimed at improving the efficient use of urban land. Improving the efficient use of urban land is imperative to address land prices and housing shortages, protecting farmland and ecosystems, and mainly to tackle land hoarding, urban sprawl and informal settlements.
Keywords: 710; Determinant; Expansion; Gondar; Informal settlement; Principal component analysis